Phenotypic and molecular characterisation of breast ductal carcinoma in situ - Abdelaziz, Islam Mohammed Samy Miligy (2019)
Background Ductal carcinoma in situ (DCIS) comprises more than 20% of screen-detected breast cancer cases. The current understanding of the biology and clinical behaviour of DCIS and prediction of its progression to invasive disease remains incomplete. Treatment modalities vary; however, in most cases it involves surgical excision with or without adjuvant radiotherapy and endocrine therapy. To date, predictors of DCIS progression are not well defined; therefore, the aim of the current study was to characterise a large cohort of DCIS with long term follow-up data and identify possible predictors of DCIS outcome.